Long-term clinical outcomes of biodegradable polymer drug eluting stents versus second-generation durable polymer drug eluting stents for ST-segment elevation myocardial infarction - Sim, HW (Elsevier BV, 2021)
10.1016/j.carrev.2021.04.014